Use of medications by pregnant women in the Family Health Strategy in the Northeast of Brazil - Hudson Manoel Nogueira Campos; Mússio Pirajá Mattos; Daiene Rosa Gomes (Instituto Materno Infantil de Pernambuco, 2023)
Abstract Objectives: To evaluate the medication use, exposure to potential risks, and associated factors before and during pregnancy of pregnant women receiving care at the Family Health Strategy in a municipality in the Northeast of Brazil. Methods: This is a cross-sectional study of pregnant women receiving care in the municipality of Barreiras, in Bahia, Brazil. In data analysis process, prevalence and frequency of medication use were estimated. To investigate the association between variables, the outcome measure was expressed by the prevalence ratio (crude and adjusted) with a 95% confidence interval via Poisson regression. Results: The prevalence of medication use before pregnancy was 35% and during pregnancy, it was 80.7%. Analgesics and antianemics were the prevalent groups of medications before and during pregnancy, respectively. Family income (≤1 minimum wage; PR=1.62; CI95%=1.02-2.55) showed an association with prior use; health problems (PR=2.3; CI95%=1.27-4.22) and complaints in pregnancy (PR=2.39; CI95%=1.28-4.47) had an association with use during pregnancy. Conclusion: The characterization of a high prevalence of use of medicines by pregnant women, combined with a trend of failures in family planning could demonstrate the exposure of the risks of using some harmful substances in periods close to conception and pregnancy.